Development and validation of the Measure of Initial Attraction (MIA) - Rodrigues, D. (2015)
Unilateral Initial Attraction (UIA) is a first unilateral awareness towards an unknown person and can be the starting point of an interest in voluntarily initiating an interaction or relationship. In order to create a measure tapping this feeling, Study 1 asked individuals to indicate attributes characterizing UIA (Phase 1), and to rate their centrality (Phase 2). These were used to develop the Measure of Initial Attraction (MIA) comprising one component of arousal and another of unilateral interest. While the former is shared with the love construct, the latter differentiates from measures of passion. The MIA proved to be a valid and reliable instrument with the capacity to discriminate UIA across different relationships (Study 2) and targets (Study 3), with good convergent validity (Study 3). Results are discussed within the framework of personal relationships.